Emotional intelligence, spiritual intelligence and psychological well-being : impact on society - Nurshahira Ibrahim,; Norhapizah Mohd Burhan,; Asjad Mohamed,; Maziah Mahmud,; Sakinatul Raadiyah Abdullah, (Penerbit Universiti Kebangsaan Malaysia, 2022)
Mental health issues are frequently ignored and overlooked by society because they cannot be physically expressed. Furthermore, this perception has long been entrenched in the Malaysian society as the stigma against individuals who suffer from this problem remains at the same level even though awareness about mental health issues has spread significantly. Therefore, this study was conducted to evaluate the relationship between emotional intelligence, spiritual intelligence and psychological well-being among counseling clients in one of the government agencies in Pahang, Malaysia, during the Covid-19 pandemic. A total of 157 counseling clients answered the questionnaire. SmartPLS was used to evaluate the data content of the questionnaire and test the research hypotheses. The results of the analysis yielded several significant findings. First, there was a positive and significant relationship between emotional intelligence (i.e., self-awareness, social awareness and emotional receptivity) and spiritual intelligence. Second, there is a positive and significant relationship between emotional intelligence and psychological well-being. Third, there is a positive and significant relationship between spiritual intelligence and psychological well-being. Fourth, there is a positive and significant relationship between emotional intelligence, spiritual intelligence and psychological well-being. The findings of this study confirmed the important role of spiritual intelligence as a mediating variable in the relationship between emotional intelligence and psychological well-being. Furthermore, the findings of this study can be used as essential recommendations to help practitioners understand the diversity of perspectives on the construct of emotional intelligence and develop a spiritual intelligence management plan in counseling sessions to help those with mental issues achieve and maintain their emotional well-being in daily life.